Food safety measures and food security of smallholder dairy farmers: Empirical evidence from Bihar, India - Kumar, Anjani; Mishra, Ashok K.; Saroj, Sunil; Sonkar, Vinay Kumar; Thapa, Ganesh; Joshi, Pramod Kumar (John Wiley & Sons, 2020)
Using farm‐level data from dairy farmers in India's Bihar state and the two‐stage residual inclusion method, this study investigates the impact of the adoption of food safety measures (FSMs) on milk yield and profitability of smallholder dairy farms. This study reveals that herd size and experience in dairy farming have a significant effect on the number of FSMs smallholders adopt. An additional FSM increases milk yield by about 1% and profitability by about 2.3%. An extra year of education increases yield and profits by about 3.8% and 4.9%, respectively. The government could design and incentivize policies that help increase herd size and promote better housing conditions for animals, thus promoting the uptake of FSMs and increased milk yield and profitability. [EconLit Citations: Q12, Q16, Q18].